Pengaruh Iklim Organisasi Terhadap Kinerja Karyawan - Rt Nindica Azalea Nuryasmin; Harmon Chaniago (Jurnal Riset Bisnis dan Investasi, 2016)
Creating a climate of an organization capable of bringing the employees in a company to create a high performance is not an easy thing. This is because basically, humans have different characteristics according to his needs. Although those cases, human resources should have a good performance. One way to improve the performance of employees is to pay attention to organizational climate. This study aims to determine the organizational climate on employee performance office of PT Ultrajaya Milk Industry and Trading Company. Organizational climate measurements include the dimensions of the structure, standards, support, recognition, responsibility, and commitment. While the measurement of employee performance using the dimensions of the work, work behavior, and personal qualities. The study uses quantitative methods and involved 126 respondents drawn from employees of the office. Data was collected by questionnaire were then analyzed using descriptive statistics. The analysis includes the analysis of assumptions used classic, descriptive analysis, correlation analysis, regression analysis and coefficient of determination. Based on the research results, the level of organization climate is in the category of "good" because it has the average (mean) 3.95. So too for the performance level of employees in the category of "good" because it has the average (mean) 4.10. The results of this study indicate that organizational climate can contribute to employee performance (²) by 64%. Organizational climate is predicted to improve employee performance (positive). It can be seen from the results of the regression analysis is Y = 0.476 + 0,800X which means that if the model the characteristics of employment increased by one, the organizational commitment of employees will increase by 0,800. In addition, the organizational climate can significantly improve employee performance, it's based on figures significance probability of 0.000 smaller than 0.05.